THE EFFECT OF COMBINATIONS OF GROWTH FACTORS AND HYALURONIC ACID ON THE PROLIFERATION AND CHONDROGENIC DIFFERENTIATION OF HUMAN SYNOVIUM DERIVED MESENCHYMAL STEM CELLS - Zhubanova, G.; Mukhambetova , A.; Karzhauov , M.; Issabekova , A.; Raimagambetov , E.; Ogay , V. (Eurasian Journal of Applied Biotechnology, 2022)
Growth factors and hyaluronic acid (HA) have been shown to stimulate functional activity of mesenchymal stem cells (MSCs) and thus may influence damaged tissue healing, including cartilage. In this study we investigated the effects of individual and combinatorial application of HA, platelet derived growth factor–BB (PDGF-BB), transforming growth factor β1 (TGF-β1), bone morphogenetic protein-4 (BMP-4) and fibroblast growth factor-2 (FGF-2) on the proliferation and chondrogenic differentiation of human synovium derived MSCs (SD MSCs). Isolated SD MSCs were expanded in α-MEM medium and characterized using immunocytochemistry, multilineage differentiation assay and CFU-assay. Proliferation activity of MSCs was examined with MTT-assay. Chondrogenic differentiation and glycosaminoglycan level in micro-pellet culture of MSCs were evaluated with histochemical and biochemical analysis. Our results showed that the individual use of FGF-2 and PDGF-BB significantly increased the rate of MSC proliferation compared to the control. At the same time, TGF-β1 did not affect cell growth. Combinations of growth factors: TGF-β1+FGF-2, TGF-β1+PDGF-BB, and FGF-2+PDGF-BB were able to significantly increase the proliferative activity of MSCs. The greatest synergistic effect was found with combination of all three factors TGF-β1, FGF-2, and PDGF-BB. Histochemical and biochemical analysis revealed that combination of TGF-β1 and BMP-4 have a significant effect on chondrogenic differentiation and the synthesis of glycosaminoglycans in micro-pellet culture of MSCs. The addition of HA to growth factors has minor effect on the proliferation and does not affect the chondrogenic differentiation of MSCs. This study demonstrated that combination of growth factors can promote proliferation and chondrogenic differentiation of SD MSCs and may be effective in enhancing cartilage healing.